1972
DOI: 10.1177/104649647200300406
|View full text |Cite
|
Sign up to set email alerts
|

Nonverbal Communication and Counselor Education

Abstract: Verne was five minutes early for this session... he was able to keep eye contact when the discussion was about others. He looked down or toward the wall when the conversation was brought back to him He demonstrated his uneasiness by his switching from side to side in his chair, first crossing his legs one way and then another; his hands wrestled with each other as usual.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1973
1973
1995
1995

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Implications for counselor training and practice are discussed.Counseling theorists and practitioners seem to have commonly assumed that the interaction between verbal and nonverbal cues is a very important part of the overall communication process. Nevertheless, much of the training literature in the counseling field (Delaney & Eisenberg, 1972;Egan, 1975;Hackney & Nye, 1973), as well as actual training programs (Colwell, 1968;Heimann & Heimann, 1972), seem to have largely associated the concept of communication with a verbal-linguistic model.Only in the last few years have researchers begun to explore the process of inconsistent communication within the counseling therapy situation. Several of these studies have demonstrated the considerable impact of the nonverbal channel on the communication process in counseling.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Implications for counselor training and practice are discussed.Counseling theorists and practitioners seem to have commonly assumed that the interaction between verbal and nonverbal cues is a very important part of the overall communication process. Nevertheless, much of the training literature in the counseling field (Delaney & Eisenberg, 1972;Egan, 1975;Hackney & Nye, 1973), as well as actual training programs (Colwell, 1968;Heimann & Heimann, 1972), seem to have largely associated the concept of communication with a verbal-linguistic model.Only in the last few years have researchers begun to explore the process of inconsistent communication within the counseling therapy situation. Several of these studies have demonstrated the considerable impact of the nonverbal channel on the communication process in counseling.…”
mentioning
confidence: 99%
“…Counseling theorists and practitioners seem to have commonly assumed that the interaction between verbal and nonverbal cues is a very important part of the overall communication process. Nevertheless, much of the training literature in the counseling field (Delaney & Eisenberg, 1972;Egan, 1975;Hackney & Nye, 1973), as well as actual training programs (Colwell, 1968;Heimann & Heimann, 1972), seem to have largely associated the concept of communication with a verbal-linguistic model.…”
mentioning
confidence: 99%